MicroRNA in medication related osteonecrosis of the jaw: a review - Mohd Yunus, Siti Salmiah; Soh, Hui Yuh; Abdul Rahman, Mariati; Peng, Xin; Guo, Chuanbin; Ramli, Roszalina (Frontiers in Physiology, 2023)
Medication related osteonecrosis of the jaw (MRONJ) is a condition caused by inhibition of the osteoclast activity by the anti-resorptive and anti-angiogenic drugs. Clinically, there is an exposure of the necrotic bone or a fistula which fails to heal for more than 8 weeks. The adjacent soft tissue is inflamed and pus may be present as a result of the secondary infection. To date, there is no consistent biomarker that could aid in the diagnosis of the disease. The aim of this review was to explore the literature on the microRNAs (miRNAs) related to medication related osteonecrosis of the jaw, and to describe the role of each miRNA as a biomarker for diagnostic purpose and others. Its role in therapeutics was also searched. It was shown that miR-21, miR-23a, and miR-145 were significantly different in a study involving multiple myeloma patients as well as in a human-animal study while miR-23a-3p and miR-23b-3p were 12- to 14-fold upregulated compared to the control group in an animal study. The role of the microRNAs in these studies were for diagnostics, predictor of progress of MRONJ and pathogenesis. Apart from its potential diagnostics role, microRNAs have been shown to be bone resorption regulator through miR-21, miR-23a and miR-145 and this could be utilized therapeutically.